Comparative toxicity reduction potential of UV/sodium percarbonate and UV/hydrogen peroxide treatments for bisphenol A in water: An integrated analysis using chemical, computational, biological, and metabolomic approaches. (15th February 2021) - Gao, Jiong; Song, Jie; Ye, Jinshao; Duan, Xiaodi; Dionysiou, Dionysios D.; Yadav, Jagjit S.; Nadagouda, Mallikarjuna N.; Yang, Lixia; Luo, Shenglian
Highlights: QSAR analysis generated various toxicity indices for BPA transformation products. E. coli bioassays revealed the cellular toxicity of treated BPA solutions. Benzoquinone analogues had unique impact on cellular activities. Eight impacted metabolic pathways were identified and connected. UV/SPC had advantage of attenuated butanoate metabolism over UV/H2 O2 . Abstract: Bisphenol A (BPA) is a common industrial chemical with significant adverse impacts on biological systems as an environmental contaminant. UV/hydrogen peroxide (UV/H2 O2 ) is a well-established technology for BPA treatment in water while UV/sodium percarbonate (UV/SPC) is an emerging technology with unclear biological impacts of treated effluent. Therefore, in this study, the toxicity evaluation of BPA solution treated with UV/H2 O2 and UV/SPC was preformed and compared based on transformation products (TPs) profile, quantitative structure-activity relationship (QSAR), Escherichia coli ( E. coli ) toxicity assays, and metabolomic analysis. TPs with hydroxylation, double-ring split, and single-ring cleavage were generated from BPA during the treatments with both technologies, but TPs with quinonation were specifically detected in UV/H2 O2 treated solution at the UV dose of 1470 mJ cm −2 . QSAR prediction based on TPs profile (excluding benzoquinone TPs) suggested that UV/H2 O2 and UV/SPC treatments of BPA may increase matrix toxicity due to the formation of multi-hydroxylated TPs; however decreased bioaccumulation potential of all TPs may mitigate the increase of toxicity by reducing the chance of TPs to reach the concentration of toxicity threshold. In vivo assays with E. coli showed inhibited cell growth, arrested cell cycle, and increased cell death in BPA solution treated with UV/H2 O2 at the UV dose of 1470 mJ cm −2 . Metabolomic analysis indicated that BPA solution treated with UV/H2 O2 at UV dose of 1470 mJ cm −2 impacted E. coli metabolism differently than other solutions with unique inhibition on glycerolipid metabolism. Moreover, BPA interfered in various metabolic pathways including alanine, aspartate and glutamate metabolism, starch and sucrose metabolism, pentose phosphate pathway, and lysine degradation, which were mitigated after the treatments. UV/SPC showed advantage over UV/H2 O2 of attenuated impact on butanoate metabolism with UV irradiation. This study has generated valuable data for better understanding of biological impacts of BPA and its solutions treated with UV/H2 O2 or UV/SPC, thus providing insights for their application prospect for water and wastewater treatment. Graphical abstract: Image, graphical abstract